Radiocarbon age model of sediment core RAPiD-35-14P - Paola Moffa-Sanchez; Ian R Hall; David J R Thornalley; Stephen Barker; Connor Stewart (PANGAEA, 2019)
Changes in the vigour of the overflows may have had important climatic effects in the past and may also have in the future. We present sortable silt mean grain size data, as a proxy for near-bottom current speed, from sub-decadal to decadally resolved sediment cores located in the direct pathway of the two Nordic Overflows east and west of Iceland, the Iceland-Scotland Overflow Water (ISOW) and the Denmark Strait Overflow Water (DSOW) spanning the last 3000-4000 years. The cores were recovered from the South Iceland Rise (RAPiD-17-5P) and the Eirik Drift (RAPiD-35-COM) and their core-chronologies were constructed using radiocarbon dating. The sortable silt was measured using the Multisizer Coulter Counter 3 and the data presented consisted of the average of three different measurements.
Supplement to: Moffa-Sanchez, P et al. (2015): Changes in the strength of the Nordic Seas Overflows over the past 3000 years. Quaternary Science Reviews, 123, 134-143, https://doi.org/10.1016/j.quascirev.2015.06.007